The Effect of Providing Incentives Towards Increased Employee Productivity at PT. XYX - Sartika Sinaga (Institute of Computer Science (IOCS), 2018)
The analytical method used in this research is descriptive and deductive method and calculation method with correlation that is to see whether there is a relationship between providing incentives with the productivity obtained / achieved by labor. From the results of the analysis and evaluation the following conclusions are obtained: 1.The system of providing incentives implemented by PT. Xyz is already quite effective. 2.The types of incentives provided by the company are medication and care, sick day assistance, annual leave, maternity leave, menstrual leave. Food allowance, overtime, overtime week / holiday, social security, education and training, bonuses and THR. 3. Each increase and decrease in incentives (X) will affect the increase / decrease in the level of productivity (Y). Where the relationship is 0.9993 (very strong) and the contribution of incentives to employee work productivity is 96.86%. The suggestions put forward by the author to help company managers are as follows: 1. In addition to providing incentives, companies need to pay attention to other factors such as: education and training, motivation, discipline and work ethics, work environment and climate, wages and social security levels, technology and production facilities, nutrition and health as well as achievement attention. 2. Company leaders should increase food and transportation fees periodically because the current meal and transport fees have not been interested for a long time and are no longer appropriate to the current level of needs.